Cover Image, Volume 118, Number 7, July 2017. Issue 7 (July 2017) - Dholpuria, Sunny; Kumar, Manish; Kumar, Sandeep; Sarwalia, Parul; Rajput, Sandeep; Kumar, Rakesh; De, Sachinandan; Datta, Tirtha K.
Abstract : Cover : The cover image, by Tirtha K. Datta et al., is based on the Article Differential Expression of Newly Identified Long Intergenic Non‐Coding RNAs in Buffalo Oocytes Indicating Their Possible Role in Maturation and Embryonic Development, DOI:10.1002/jcp.25828 .